(ψ,α,β)-Weak Contraction in Partially Ordered G-Metric Spaces: M. Bousselsal, Z. Mostefaoui - Team, Support (Thai Journal of Mathematics, 2014)
In this paper we have generalized the weak contraction principle to coincidence point and common fixed point results in partially ordered G-metric spaces. We illustrate our results with the help of an example.